Biodegradation of aflatoxin B1 by a novel mined aldo–keto reductase from Meyerozyma guilliermondii AF01 - Wan Zhang; Xiaojiao Chang; Yangying Han; Tiantian Li; Jianpeng Dou; Wen Du; Wenfu Wu; Wei Wang; Zhongjie Zhang; Changpo Sun (Biological Control)
Biocontrol is an effective technology for managing mycotoxin contamination in food, and the improvement of its application depends largely on revealing the degradation mechanisms at the molecular level. Research in this area is much less than that on the screening of degrading strains. In a previous study, Meyerozyma guilliermondii AF01 was confirmed to exert degradation and adsorption effects on aflatoxin B1 (AFB1). In this study, a potential degradation gene, MG2-4, was mined using a combination of bioinformatics and chemical approaches. The gene was heterologously expressed in Escherichia coli Rosetta DE3, and the recombinant protein, Mg aldo–keto reductase (AKR), reacted with AFB1 in vitro. Moreover, MgAKR rapidly removed AFB1. The degradation product was identified as aflatoxicol using ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry, which is the same as the degradation product of the AF01 strain. This study reveals that MG2-4 is the key AFB1-degrading enzyme gene in the AF01 strain and lays the foundation for improving AFB1 removal using the AF01 strain.